Economic applications of the theory of graphs - Avondo-Bodino, Giuseppe (New York : Gordon and Breach, Science Publishers, 1962)
The book aims to acquaint the reader with a group of economic problems relating to business management and to economic policy in general. The author intends to solve them by means of a method based strictly on topological considerations. This method frequently affords considerable advantages over the analytic procedures which, generally, are better known and, hence, applied more extensively.
Includes index
Includes bibliographical references: p. 107-108.
aia 10/04/2018
Loans
Keywords: Graphic method; Industrial management; Economics $1 (BMethodology.s